2020
DOI: 10.1007/s00382-020-05224-3
|View full text |Cite
|
Sign up to set email alerts
|

Identification of major moisture sources across the Mediterranean Basin

Abstract: We employ a Lagrangian based moisture back trajectory method on an ensemble of four reanalysis datasets to provide a comprehensive understanding of moisture sources over the Mediterranean land region (30° N-49.5° N and 9.75° W-61.5° E) at seasonal timescales for 1980-2013 period. Using a source region between 10° S-71.35° N along the latitude and 80° W-84.88° E along the longitude that is subdivided into ten complimentary sub-regions, our analyses is able to backtrack up to > 90% of seasonal precipitation at e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 59 publications
4
10
0
Order By: Relevance
“…This is consistent with the findings of Batibeniz et al. (2020) who showed that the eastern Mediterranean, as being a source of moisture, plays a significant role in shaping the precipitation pattern in the surrounding regions during spring and summer. In the southern parts of the NE, the Gulf of Aden and the Red Sea also show relatively large IVT (160–200 kg m −1 s −1 ) with a southwesterly flow shaped by the subtropical anticyclone over the Arabian Peninsula, at the eastern flank of the Red Sea, which is known as the the Arabian anticyclone at lower‐ and middle‐tropospheric levels (e.g., de Vries et al., 2016; Raziei et al., 2012).…”
Section: Resultssupporting
confidence: 93%
“…This is consistent with the findings of Batibeniz et al. (2020) who showed that the eastern Mediterranean, as being a source of moisture, plays a significant role in shaping the precipitation pattern in the surrounding regions during spring and summer. In the southern parts of the NE, the Gulf of Aden and the Red Sea also show relatively large IVT (160–200 kg m −1 s −1 ) with a southwesterly flow shaped by the subtropical anticyclone over the Arabian Peninsula, at the eastern flank of the Red Sea, which is known as the the Arabian anticyclone at lower‐ and middle‐tropospheric levels (e.g., de Vries et al., 2016; Raziei et al., 2012).…”
Section: Resultssupporting
confidence: 93%
“…The difference of E in Fig. 4 d is indicative of larger values in the MME than in REF over nearly all ocean areas with a pronounced maximum difference in the Mediterranean, which is in line with an evaluation study of Mediterranean Sea water and heat budgets 58 and the E and P relationships in the eastern Mediterranean 63 . Differences between MME and REF over land are relatively small and might be attributed to differences in the landmask (close to the coast), landuse datasets (see, e.g., Southern Spain), or the RCMs’ land surface model.…”
Section: Resultssupporting
confidence: 88%
“…Figure 4 g gives insight in the spatial distribution of source and sink areas of the atmospheric water balance. Independent of lateral in- or outflow of atmospheric moisture, the Mediterranean and southern parts of the Eastern Atlantic with the Azores High are net source areas of atmospheric moisture while continental areas act as net sinks, which is well-known 53 , 58 , 63 , 65 . In case of ocean areas, the difference of the E O – P O atmospheric water balances of MME and REF (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Note that, over this period, the intertropical convergence zone gradually moves southward over southwest Africa (away from the AP) and back over Eastern Africa (Ashfaq et al, 2021). Some syncing is also noticed between moisture from the Mediterranean/Caspian Seas and the North Atlantic, which is understandable as similar dynamical characteristics in uence the movements of storm tracks and moisture from the Mediterranean and beyond (Batibeniz et al, 2020). However, it is interesting to note that moisture contribution from Europe gradually increases over the wet season and reaches its maximum at a time when moisture supply from North Atlantic, Mediterranean/Caspian Seas depletes.…”
Section: Characteristics Of Primary Moisture Sourcesmentioning
confidence: 71%